Structured interview for tourism experts (Melaka UNESCO World Heritage Site) - Ab Rahman, Syakir Amir (2020)
Structured interview questions booklet was designed to interview 20 tourism experts in Melaka UNESCO World Heritage Site that involves government officers, tourism business operators in five main industries. The diary record survey is one of the quantitative data collection methods in research process.